The Role of Generative Artificial Intelligence as a Financial Assistant in MSME Financial Decision-Making in Gorontalo Province - Hamka Hamka; Zumran Ibrahim (Review: Journal of Multidisciplinary in Social Sciences, 2026)
The study aims to analyze the use of generative artificial intelligence as a financial assistant and its role in supporting the quality of financial decision-making among MSME actors in Gorontalo Province. This research employed a qualitative descriptive approach, with informants selected purposively from MSME actors who had utilized generative AI in their business activities. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that generative AI assists MSME actors in preparing budgets, recording transactions, analyzing cash flow, calculating profits and losses, and generating alternative financial solutions. The use of this technology also improves administrative efficiency and helps business owners understand their financial conditions more systematically. However, its effectiveness depends on digital literacy, financial literacy, the ability to provide clear instructions, and the verification of AI-generated information. Therefore, generative AI should be positioned as a decision-support tool that complements human judgment rather than replacing it. This study implies that strengthening digital and financial literacy is essential to optimize the adoption of generative AI and improve the competitiveness of MSMEs in the digital era.